SWOT Analysis–Based Development Strategy for Sea Turtle Conservation Tourism Attraction at Pangumbahan Turtle Park, Sukabumi - Nicholas Daniel Gunawan; Imam Ardiansyah (Darul Yasin Al Sys, 2026)
Sustainable tourism integrating conservation-based ecotourism principles is essential for balancing the utilization of natural resources with the protection of coastal ecosystems. This study aimed to examine the existing conditions of Pangumbahan Turtle Park, Sukabumi Regency, and formulate strategies for developing its tourism attractions while maintaining its function as a nesting habitat for green sea turtles (Chelonia mydas). A descriptive qualitative design was employed using the 4A tourism components framework—Attraction, Accessibility, Amenity, and Ancillary Services—combined with SWOT analysis. Data were collected through field observations, documentation, and in-depth interviews with purposively selected destination managers, local community members, and tourists. The data were analyzed using the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices to identify the internal and external factors influencing destination development. The findings show that Pangumbahan Turtle Park obtained an IFAS score of 3.07 and an EFAS score of 3.08. The SWOT analysis positioned the destination in Quadrant I at coordinates of 1.93 and 1.88, indicating strong internal capacity and favorable external opportunities that support the implementation of a growth-oriented strategy. The recommended strategies include developing conservation education tourism programs, optimizing digital marketing, strengthening partnerships with educational institutions, improving supporting facilities, and reinforcing destination management regulations. The study concludes that Pangumbahan Turtle Park possesses substantial potential for sustainable tourism development, provided that destination growth is consistently aligned with conservation priorities. These findings contribute a strategic framework for developing conservation-based coastal tourism and provide practical guidance for destination managers and local stakeholders in strengthening ecological protection, visitor experiences, institutional collaboration, and long-term destination sustainability.